A Novel Design of Non-Uniform Limited Scan Array Based on Tri-Polarized Metamaterial Element - Jianqing Sun; Ke Zhang; Jianyu Ye; Xiaoliang Wu; Guang Hua (IEEE Access)
Limited scan arrays have attracted a lot of attentions in recent years, due to its many merits, such as fewer array elements, lower weight and easy heat dissipation of transmit and receive(T/R) channels. In the conventional literature, the subarray is usually chosen as the radiation element, however the subarray need an additional passive feeding network, which will cause an additional insertion loss and cost. Also, as far as we know, the grating lobes caused by large array element spacing haven’t been perfectly eliminated in the published literature. In this paper, we firstly design a tri-polarized metamaterial element with the “flat-top” pattern, and then design a non-uniform linear limited scan array with large spacing based on the proposed metamaterial element. Measurement results demonstrate that the metamaterial element exhibits nearly identical voltage standing wave ratio and radiation patterns under excitation for all three polarizations, indicating promising application prospects in polarization-diversity radar. Furthermore, simulation results indicate that this element also exhibits a certain level of grating lobe suppression effect in large-element-spacing, non-uniform linear arrays within the limited-scan domain.